2014
DOI: 10.1165/rcmb.2013-0411oc
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Benzenediamine Derivate Rescued Mice from Experimental Sepsis by Attenuating Proinflammatory Mediators via IRAK4

Abstract: We designed and synthesized a novel benzenediamine derivate, FC-99, that was tested for its ability to protect mice from experimental sepsis. Moreover, we sought to determine whether FC-99 could control a bacterial infection and to clarify the mechanism by which FC-99 inhibited LPS-activated macrophages. The effects of FC-99 on inflammation were evaluated in two experimental sepsis models and in cultured macrophages. Microarrays and docking and molecular dynamics simulations were used to determine the target o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…In the CLP model group, mice displayed 100% mortality at 7 days, whereas, in the 10 mg/kg FC-99 treatment groups, the mortality rate was 32.5%, which indicated an effective improvement of the animal survival ( P < 0.001) (Figure 1A ). Furthermore, the bacterial colony forming unit (CFU) counts in the indicated groups of mice were measured in order to determine whether FC-99 alters the level of bacterial burden in the peritoneal lavage fluid and blood [ 31 ], which were collected 24 hours following the CLP operation. The results indicated that the bacterial CFU counts in the peritoneal lavage fluid and blood of the septic mice were significantly increased ( p < 0.005) compared with the sham-operated mice.…”
Section: Resultsmentioning
confidence: 99%
“…In the CLP model group, mice displayed 100% mortality at 7 days, whereas, in the 10 mg/kg FC-99 treatment groups, the mortality rate was 32.5%, which indicated an effective improvement of the animal survival ( P < 0.001) (Figure 1A ). Furthermore, the bacterial colony forming unit (CFU) counts in the indicated groups of mice were measured in order to determine whether FC-99 alters the level of bacterial burden in the peritoneal lavage fluid and blood [ 31 ], which were collected 24 hours following the CLP operation. The results indicated that the bacterial CFU counts in the peritoneal lavage fluid and blood of the septic mice were significantly increased ( p < 0.005) compared with the sham-operated mice.…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting was performed according to previously described methods . Protein concentrations were determined using a Bradford assay (Pierce, Thermo Scientific, Rockford, IL, http://www.thermoscientific.com).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the natural IRAK4 inhibitors mentioned above, the synthetic benzenediamine FC-99 ( Figure 8 ) was proven to bind to IRAK4 both in silico and in vitro (SPR assay) [ 148 ]. FC-99 protected mice in the CLP-induced polymicrobial sepsis model and significantly decreased the serum levels of TNF-α and IL-6.…”
Section: Synthetic Tlr4 Antagonistsmentioning
confidence: 99%